2022
DOI: 10.1111/vde.13097
|View full text |Cite
|
Sign up to set email alerts
|

Fatal disseminated toxoplasmosis in a feline immunodeficiency virus‐positive cat receiving oclacitinib for feline atopic skin syndrome

Abstract: Toxoplasma gondii is a ubiquitous protozoan, for which felids are the definitive host. Immunocompromised individuals are susceptible to recrudescent toxoplasmosis. This case describes a 6-year-old, feline immunodeficiency virus-positive domestic short hair cat with feline atopic skin syndrome that developed fatal toxoplasmosis after treatment with oclacitinib for five months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Additionally, a recent case report described a feline immunodeficiency virus‐positive cat with pruritus that was treated with oclacitinib at a dose of 1 mg/kg twice daily for five months due to concerns over the immune‐modulating effects of licensed treatments such as glucocorticoids or ciclosporin. While oclacitinib was clinically effective, the cat developed clinical signs associated with disseminated toxoplasmosis, resulting in a fatal outcome 22 …”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent case report described a feline immunodeficiency virus‐positive cat with pruritus that was treated with oclacitinib at a dose of 1 mg/kg twice daily for five months due to concerns over the immune‐modulating effects of licensed treatments such as glucocorticoids or ciclosporin. While oclacitinib was clinically effective, the cat developed clinical signs associated with disseminated toxoplasmosis, resulting in a fatal outcome 22 …”
Section: Commentsmentioning
confidence: 99%
“…While oclacitinib was clinically effective, the cat developed clinical signs associated with disseminated toxoplasmosis, resulting in a fatal outcome. 22 One placebo-controlled study also reported the use of oclacitinib in cats without skin disease, aiming to determine adverse events in cats receiving the drug at either 1 mg/kg or 2 mg/kg daily for 28 days. 23 Two of the 10 cats in the 2 mg/kg group experienced transient vomiting and two had soft stools, but no gastrointestinal signs were seen in the 1 mg/kg group.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…At 2 mg/kg twice daily vomiting and soft stools were reported (Lopes and others 2019). A case of fatal disseminated toxoplasmosis has also been reported in an FIV‐positive cat that was prescribed oclacitinib (Moore and others 2022).…”
Section: Managementmentioning
confidence: 91%
“…Fatal toxoplasmosis has been reported in a feline immunodeficiency virus-positive cat receiving oclacitinib. 41 Toxoplasmosis has been reported also in cats receiving cyclosporine. 39,[42][43][44] For the efficacy and doses of oclacitinib used in feline studies, see Table 3.…”
Section: Use In Feline Atopic Skin Syndromementioning
confidence: 99%